Hepatic sclerosed hemangioma with special attention to diffusion-weighted magnetic resonance imaging - Tatsunori Miyata; Toru Beppu; Kunitaka Kuramoto; Shigeki Nakagawa; Katsunori Imai; Daisuke Hashimoto; Tomohiro Namimoto; Yo-ichi Yamashita; Akira Chikamoto; Yasuyuki Yamashita; Hideo Baba (Surgical Case Reports)
Abstract Background A hepatic sclerosed hemangioma (HSH) is a very rare benign liver tumor. The correct preoperative diagnosis of HSH is very difficult because its features of imaging are similar to those of intrahepatic cholangiocarcinoma or colorectal liver metastasis. Case presentation We experienced five patients who were diagnosed histologically with HSH. The preoperative diagnoses were HSH in two patients, cavernous hemangioma in one, intrahepatic cholangiocarcinoma in one, and colorectal liver metastasis in one. All patients were treated with hepatectomy (one laparoscopic and four laparotomies), and the diagnosis was completed by histological investigation of the resected specimen. In particular, we investigated the apparent diffusion coefficient (ADC) mean value using diffusion-weighted sequences of magnetic resonance imaging (DW-MRI). The average of the ADC mean (ADCmean) value of HSH was 1.94 × 10−3 mm2/s (range 1.73–2.10 × 10−3 mm2/s), which was higher than the value of common malignant liver tumors. Interestingly, the ADCmean values were almost the same between the degenerate (1.90 ± 0.17 × 10−3 mm2/s) and the non-degenerate areas (1.95 ± 0.26 × 10−3 mm2/s) in HSH. Conclusions The ADCmean value seemed to be quite useful to preoperatively distinguish HSH from other malignant liver tumors.